Regional Variations in Correlation between Photopic Negative Response of Focal Electoretinograms and Ganglion Cell Complex in Glaucoma. (27th May 2014) - Machida, Shigeki; Kaneko, Muneyoshi; Kurosaka, Daijiro
Abstract: Purpose : To determine regional variations in a structure-function relationship, we correlated the the photopic negative response (PhNR) of the focal electoretinogram (ERG) with the ganglion cell complex (GCC) thickness in different retinal regions in patients with open angle glaucoma (OAG). Methods : Fifty-one eyes of 51 OAG patients (OAG group) and 17 eyes of 17 normal volunteers (control group) were studied. The OAG patients had different degrees of glaucoma ranging from early to advanced stages. The focal ERGs were elicited by a white, 15° hemispherical stimulus placed superior or inferior to the fovea. Focal ERGs were also elicited by a half annulus placed superior or inferior to the macular region. The diameter of the inner border of the annulus was 15° and that of the outer border was 30°. The average GCC thickness in areas corresponding to the location of the stimuli was measured in SD-OCT images. Results : The PhNR amplitude and PhNR/b-wave amplitude ratio were significantly correlated with the GCC thickness in the superior and inferior hemispherical areas ( p  < 0.0001). These ERG parameters were weakly correlated with the GCC thickness in the superior and inferior semi-annular areas ( p  < 0.05). There were significant differences in the slopes of the regression lines plotting the GCC thickness and the PhNR amplitude or the PhNR/b-wave amplitude ratio between the spherical and semi-annular areas (superior: p  < 0.01, inferior: p  < 0.0005). Conclusions : The thinning of the GCC affects the RGC function measured by the PhNR more strongly in the central retinal area than in the surrounding retinal areas.